Detecting Latent Prints on Stone and Other Difficult Porous Surfaces via Indanedione/Zinc Chloride and Laser - Shiquan LIU; Zhongliang MI; Jian Wu; Brian Dalrymple (Wolters Kluwer Medknow Publications, 2016)
Lasers and alternate light sources have been recognized as effective tools for latent print detection for over three decades. Luminescence often increases friction ridge contrast to reveal impressions otherwise undetectable. Indanedione/zinc chloride excited by a forensic light source is widely recognized as an effective process for developing latent prints on porous surfaces. This study was designed to evaluate the use of a combination of luminescence excitation and indanedione with zinc chloride to detect latent prints on stones, bricks, and similar difficult porous surfaces. The wavelengths evaluated included 400 nm (violet), 447 nm (blue), 532 nm (green), and 645 nm (red). Latent prints were deposited on a variety of porous surfaces including bricks, cement stones, wood, and cotton fabric, all commonly encountered at crime scenes in China. The surfaces were examined using white light (light-emitting diode flashlight) and laser light sources separately, both before and after treatment with indanedione/zinc chloride. The goal of this study was to evaluate various light sources for their effectiveness in detecting impressions developed by indanedione/zinc chloride on difficult porous surfaces. Results indicated that latent prints on some brick and cement stone surfaces may be effectively detected using 532 nm laser excitation after indanedione/zinc chloride processing.